Is there any role of thrombin activatable fibrinolysis inhibitor in the development of a hypercoagulable state in gastric cancer - MAYADAĞLI, ALPASLAN; Eser, Mehmet; Kement, Metin; Balin, Salim; Coskun, Cihan; KEFELİ, UMUT; Gumus, Mahmut; Altuntas, Yunus Emre; Kurt, Necmi; Mayadagli, Alpaslan (My University, 2012)
Background: The purpose of this study was to investigate plasma levels of thrombin activatable fibrinolysis inhibitor (TAFI) and TAFI-s relationship with coagulation markers (prothrombin fragment 1 + 2) in gastric cancer patients.